Joseph Hugh Tuck, 1929-86: A Personal Tribute - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1987)
Pays homage to the life and work of Hugh Tuck, who taught labour history at Memorial University. Includes a list of significant publications and a photo.
Keywords: Joseph Hugh; TUCK